(untitled) (Advancing Women in Leadership Journal, 2022)
In this paper, we used a qualitative multiple case study approach. We used the authentic leadership framework (Luthans & Avolio, 2003) to examine how African American women in senior administrator roles, particularly in the president’s cabinet, at a member institution of the Association of Public and Land-Grant Universities (APLU) in Alabama describe their experiences of developing an authentic leadership style. Following previous studies and recommendations for future research (Davis, 2016; Milner, 2006; Pace, 2017; Robinson, 2017; Wiggs-Harris, 2011), the following research question guides this work: How do African American women senior administrators describe their experiences of developing a leadership style? The results of this study revealed six common themes that are related to the authentic leadership style development of African American women. Code-switching was also an interesting element that emerged from some of the interviews, which may impact how some of them may present themselves and are perceived by others. In relation to the findings, theories of authentic leadership and intersectionality are discussed along with suggestions for future research. Keywords: African American women, authentic leadership, senior administrator